Cutting and Carting Sugar Cane, Trinidad, B.W.I. - (:unkn) unknown (James Book Store, 2009)
A picture of labourers in the cane field cutting and loading the crop onto carts. The sugar factory buildings can be seen in the background. Postcard numbered S 3 - 12.
Colour: Coloured; Style: Landscape; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Sugarcane industry--Trinidad and Tobago; Sugarcane--Trinidad and Tobago; Working class--Trinidad and Tobago; Sugar factories--Trinidad and Tobago; Carriages and carts--Trinidad and Tobago